Modelo ProLab: Willarina, una propuesta sostenible para la generación de ingresos de las amas de casa en Lima Metropolitana - Alvarez Villegas, Ayling Maritsa (2025)
Willarina was presented as an innovative proposal aimed at supporting housewives in Metropolitan Lima by generating income through the sale of homemade food using company- formalized mobile food vehicles. The business model consisted of providing a digital platform that would facilitate the connection between housewives and their customers, improving the visibility and management of their businesses efficiently. This platform not only offered a technological solution but also ensured consistent support from the company for the housewives. As a result, Willarina would act as an intermediary between housewives and end consumers, charging an 18% commission on each dish sold. This structure would allow housewives to benefit from comprehensive support without incurring additional costs, enabling their participation in the market without requiring upfront investments. The model would enable entrepreneurs to focus on their core activities while receiving the necessary assistance to manage their businesses successfully. The proposal not only fostered women's economic independence and empowerment but also promoted social and environmental responsibility. Sustainable practices were implemented in workspaces, contributing to the reduction of environmental impact. The initiative aligned with Sustainable Development Goals (SDGs) 5, 8, and 12, encouraging responsible consumption and local economic development. Finally, the desirability, feasibility, and viability of the business model were validated, demonstrating its profitability and adaptability to the market. The financial analysis revealed a Net Present Value (NPV) of S/ 3,752,849 for shareholders, an Internal Rate of Return (IRR) of 163.22%, and a Social NPV of S/ 7,485,542. Additionally, a detailed implementation plan was presented, outlining an efficient strategy tailored to the needs of the Peruvian market.